Double-layer microcapsule structure flame retardant, flame-retardant polyurethane material as well as preparation method and application of flame-retardant polyurethane material
By adopting a double-layer microcapsule structure flame retardant, combined with the cupric aromatic boric acid resin, melamine phenylahydric anhydride resin and hydroxyapatite modified aluminum hypophosphate, the stain resistance, thermal stability, flammability, seawater corrosion resistance and aging resistance of polyurethane flame retardant are solved, and efficient flame retardant and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411724812.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing polyurethane flame retardants have problems such as poor stain resistance, poor thermal stability, flammability, poor seawater corrosion resistance and poor aging resistance.
A double-layer microcapsule structure flame retardant is used, the outer shell layer is a cupoaromatic boric acid resin, the middle shell layer is melamine phenylakon resin, and the core layer is hydroxyapatite modified aluminum hypophosphate. Melamine phenylahydride resin was prepared by polycondensation reaction and coated on hydroxyapatite modified aluminum hypophosphate, and then covalent bonds were formed between the caldera aromatic hydrocarbon and boric acid to achieve cross-linking and hydrophobicity enhancement.
While improving the flame retardant performance, it improves the hydrophobic properties and mechanical properties of polyurethane PU polymers, and achieves multifunctional modifications that are self-cleaning and corrosion-resistant.
Smart Images

Figure CN119591940A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a double-layer microcapsule structure flame retardant, a flame retardant polyurethane material and a preparation method and application thereof, belonging to the technical field of flame retardants. Background Art
[0002] Polyurethane (PU), as a thermoplastic resin, has the advantages of low cost, mature processing and molding technology, low thermal conductivity, high compressive strength, and easy processing. It is an important basic raw material for the development of national economy and scientific and technological progress. However, PU is extremely flammable and produces a lot of smoke, which can cause serious harm to human health, seriously affecting its application in the fields of marine pipelines, building materials, industry and injection molding. Flame retardants, as a functional additive, can give PU flame retardant properties by affecting the combustion process and combustion products, but the addition of ordinary flame retardants often reduces the mechanical properties of PU, and the specific application of PU in marine pipelines requires certain stain resistance and seawater corrosion resistance. Therefore, improving the overall flame retardancy, hydrophobicity, and seawater corrosion resistance without reducing its mechanical properties is the most economical and effective research direction to achieve high performance of PU.
[0003] Chinese invention patent CN115246860A discloses a method for preparing and using a phosphorus-nitrogen intumescent flame retardant nanosheet. In the first step, an intermediate product is obtained by a nucleophilic substitution reaction between hexachlorocyclotriphosphazene and acetaminophenol, followed by a deamidation reaction under alkaline conditions and a salt-forming reaction with phytic acid to obtain a phosphorus-nitrogen intumescent flame retardant nanosheet. In order to improve the thermal stability of the product, the patent introduces anhydride substances, which affects the flame retardant effect of the product and ultimately limits the scope of use of the product.
[0004] Chinese invention patent CN116554549A discloses a nitrogen-phosphorus high synergistic dual-functional flame retardant, a highly effective flame-retardant β-crystalline polypropylene material, and its preparation method and application. The flame retardant is composed of polyphosphate, modified polymer and chitosan, and the modified polymer is a polyphosphate-modified phytic acid-melamine supramolecular polymer. The nitrogen-phosphorus synergistic flame retardant prepared by this patented technology has poor hydrophobicity due to its outer layer being coated with chitosan, and its application in the field of marine pipelines is very limited, and its seawater corrosion resistance is poor, which limits its application. Summary of the invention
[0005] In view of the problems of poor stain resistance, poor thermal stability, flammability, poor seawater corrosion resistance and poor aging resistance of existing polyurethane flame retardants, the present invention provides a double-layer microcapsule structure flame retardant, a flame retardant polyurethane material and a preparation method and application thereof. The flame retardant can simultaneously achieve flame retardancy and excellent mechanical properties as well as multifunctional modification of self-cleaning and corrosion resistance.
[0006] In order to solve the above technical problems, the first aspect of the present invention is to provide a double-layer microcapsule structure flame retardant, comprising an outer shell layer, a middle shell layer and a core layer arranged from the outside to the inside; wherein the outer shell layer is a calixarene boric acid resin, the middle shell layer is a melamine phthalic anhydride resin, and the core layer is hydroxyapatite-modified aluminum hypophosphite. The double-layer microcapsule structure flame retardant can be prepared by the following preparation method.
[0007] The second aspect of the present invention is to disclose a method for preparing a double-layer microcapsule structure flame retardant, comprising the following steps:
[0008] SO1, add melamine aqueous solution into the reactor, add 37wt%-39wt% phthalic anhydride aqueous solution into the melamine aqueous solution, make the molar ratio of phthalic anhydride to melamine be 3:2.15-2.22, add nitrogen-containing pH regulator dropwise to adjust the pH to 8-9, react at 65-80℃ for 0.5-1.5h to obtain melamine phthalic anhydride resin prepolymer emulsion, and then add aluminum hypophosphite to melamine at a mass ratio of 3-6 : 1. According to the mass ratio of hydroxyapatite to melamine of 1:8-12, aluminum hypophosphite and hydroxyapatite are added to the melamine phthalic anhydride prepolymer emulsion, the pH is adjusted to 4-5 with an acidic pH regulator, the reaction is carried out at 70-90° C. for 4-6 hours, the mixture is allowed to stand, filtered, washed with anhydrous ethanol until neutral, and dried at 60-95° C. for 12-24 hours to obtain melamine phthalic anhydride resin-coated aluminum hypophosphite-modified microcapsules (MCAHP);
[0009] SO2, according to the mass ratio of calixarene to N,N-dimethylformamide of 1:20-40, stir at 60-90℃ for 1-2h, until the solution is clear; according to the mass ratio of calixarene to MCAHP of 1:2-4, mix, add Tween-80, stir for 0.5-1h, add boric acid according to the mass ratio of boric acid to calixarene of 1:15-20, stir, react at 80-105℃ for 5-8h, add acetone according to the mass ratio of MCAHP to acetone of 1:3-5 and stir for 30min, cool, filter, wash with acetone until neutral, dry at 80-120℃ for 24-48h, grind into powder, and obtain a double-layer microcapsule structure flame retardant.
[0010] In S01, the molar ratio of phthalic anhydride to melamine is about 3:2.2, so that phthalic anhydride and melamine react fully to form melamine phthalic anhydride resin, which enhances mechanical properties and synergistic flame retardant effect; at the same time, a part of the amino groups in melamine are reserved in an unreacted state, and the unreacted amino groups are used for subsequent cross-linking with phenolic hydroxyl groups in the calixarene cavity. Alkaline conditions are conducive to the initial polymerization of melamine and phthalic anhydride to form a prepolymer. The mass ratio of aluminum hypophosphite to melamine is 3 to 6:1, which enables melamine phthalic anhydride resin to fully cover the aluminum hypophosphite of hydroxyapatite, and the amount of melamine phthalic anhydride resin is not too large to form an overly thick melamine phthalic anhydride resin layer. The mass ratio of hydroxyapatite to melamine is 1:8 to 12, and hydroxyapatite is used to increase the mechanical properties of the core layer of the material, and can synergistically flame retard with melamine phthalic anhydride resin and aluminum hypophosphite.
[0011] In S01, when the pH is adjusted to 4-5, it is beneficial for the prepolymer to continue to polymerize and coat on the surface of aluminum hypophosphite and hydroxyapatite.
[0012] In S02, calixarene is uniformly dispersed in N,N-dimethylformamide. The mass ratio of calixarene to MCAHP is 1:2-4, because MCAHP is the main part of this flame retardant, which mainly plays a nitrogen-phosphorus synergistic flame retardant effect. A certain amount of calixarene is required to crosslink and coat MCAHP, and the amount of calixarene cannot be too large, otherwise the flame retardant effect will be reduced. Tween-80 can improve the interfacial properties of the reaction system, promote the interaction of reactants, and catalyze the reaction. The mass ratio of boric acid to calixarene is 1:15-20, and less boric acid is used to modify calixarene. Acetone can make both calixarene boric acid resin and melamine phthalic anhydride resin uniformly dispersed therein. In S02, the mass ratio of boric acid to calixarene makes the phenolic hydroxyl group of calixarene obviously excessive, and there are still surplus phenolic hydroxyl groups in the calixarene cavity for crosslinking with the amino group of melamine phthalic anhydride resin. At the same time, hydrogen bonds are formed between the amide group of melamine phthalic anhydride resin and the phenolic hydroxyl group of calixarene boric acid resin.
[0013] Similarly, aluminum hypophosphite and hydroxyapatite form hydrogen bonds with the melamine phthalic anhydride resin, respectively, which helps the melamine phthalic anhydride resin to tightly coat the core layer.
[0014] Among them, melamine is added into a reaction kettle in SO1, and deionized water is added according to the mass ratio of melamine to deionized water of 1:100-250 to obtain a melamine aqueous solution.
[0015] In SO1, the nitrogen-containing pH regulator is one of ammonia water, ammonium chloride, and ammonium carbonate; the acidic pH regulator is one of acetic acid, hydrochloric acid, and sulfuric acid. The second aspect of the present invention discloses a flame retardant polyurethane material modified with a double-layer microcapsule structure flame retardant.
[0016] Specifically, the flame retardant polyurethane material has a UL-94 flame retardant grade of V-0 and a loss on ignition LOI of 32.7-34.4%.
[0017] The third aspect of the present invention is to provide a method for preparing the aforementioned flame retardant polyurethane material, comprising the following steps: adding each component to polyurethane according to the addition amount of 10wt% to 20wt% of the double-layer microcapsule structure flame retardant, according to the addition amount of 0.5wt% to 1wt% of the silica sol, according to the addition amount of 0.1wt% to 0.25wt% of the film-forming aid, according to the addition amount of 0.1wt% to 0.25wt% of the thickener, according to the addition amount of 5wt% to 10wt% of the ion conductive agent, mixing evenly, melt blending at 160 to 200°C, and finally extruding through a twin-screw extruder, cooling and granulating to obtain the flame retardant polyurethane material. The above wt% are all mass percentages relative to the polyurethane.
[0018] Among them, the mass fraction of SiO2 in the silica sol is 20%±2%; the thickener is one of alkyl ammonium salt, gelatin or sodium carboxymethyl cellulose; the film-forming aid is one of propylene glycol, propylene glycol butyl ether, dodecyl alcohol ester or N,N-dimethylformamide N,N-dimethylformamide; the ion conductive agent is a combination of one or more of choline chloride, acetylcholine chloride and carbachol.
[0019] The fourth aspect of the present invention is to provide the use of the aforementioned double-layer microcapsule structure flame retardant or flame retardant polyurethane material in combustible gas transmission pipelines, marine pipelines and shale gas fracturing pipelines.
[0020] The invention prepares melamine phthalic anhydride resin by utilizing the polycondensation reaction principle, and uses the melamine phthalic anhydride resin to coat hydroxyapatite-modified aluminum hypophosphite to obtain MCAHP; utilizes the mutual reaction of hydroxyl groups between calixarene (CD) and boric acid (BA) to form covalent bonds, thereby realizing cross-linking, and a part of the boric acid (BA) is cross-linked and included in the cavity of the calixarene, and the other part of the boric acid is cross-linked with the main component of the calixarene; and then reacts with MCAHP to obtain a material of calixarene boric acid resin-coated MCAHP; and uses the calixarene boric acid resin as an outer shell layer, the melamine phthalic anhydride resin as a middle shell layer, and the hydroxyapatite-modified aluminum hypophosphite as a core layer to obtain a double-layer microcapsule structure flame retardant.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The double-layer microcapsule structure flame retardant not only improves the flame retardant properties, but also improves the hydrophobicity and mechanical properties of the polyurethane PU polymer.
[0023] (1) The outer shell of the double-layer microcapsule structure flame retardant is boric acid-modified calixarene, the middle shell is melamine phthalic anhydride resin, and the core layer is aluminum hypophosphite and hydroxyapatite. The outer shell provides flame retardant function while covering the middle shell and core layer, playing a hydrophobic coating role; the middle shell is melamine resin, and the resin itself is polymerized and cross-linked to provide good mechanical properties. The melamine salt also provides excellent flame retardant properties, while covering and protecting the internal inorganic flame retardant from moisture; the interior is aluminum hypophosphite and hydroxyapatite, and the phosphorus element plays a role in combining free radicals in the flame retardant process, reducing the free radical reaction generated by combustion, thereby inhibiting combustion.
[0024] (2) The cavity size of calixarene is larger than the molecular size of melamine phthalic anhydride, which is conducive to the coating effect; and the phenolic hydroxyl group at the lower edge of calixarene can cross-link with the amino group in the melamine resin and form hydrogen bonds with the amide group in the melamine resin. The combination of multiple cross-linking sites and hydrogen bonding sites can enhance the stability after coating; there is an aromatic structure in the melamine phthalic anhydride resin, which can undergo a Π-Π stacking effect with the benzene ring in the calixarene, and melamine phthalic anhydride has a strong hydrophobic effect. The hydrophobicity of the calixarene cavity is significantly stronger than that of the calixarene body. The Π-Π stacking effect synergizes with the similar hydrophobicity of the melamine phthalic anhydride and calixarene cavities to quickly attract the melamine phthalic anhydride resin into the cavity of the calixarene rather than the calixarene body, and the hydrophobic melamine phthalic anhydride resin is completely and tightly enclosed in the calixarene cavity. At the same time, the overall structure enhances its hydrophobicity, and the high hydrophobicity obtained by the synergistic effect of the shell melamine phthalic anhydride resin and calixarene boric acid resin plays an anti-fouling and self-cleaning role, and prevents aluminum hypophosphite from being damp and reducing its flame retardant properties. In addition, covalent cross-linking and hydrogen bonding can make the coating tighter overall, enhance hydrophobicity and mechanical properties, and the carbonized layer formed during combustion is also tighter, which synergistically improves the flame retardant effect.
[0025] (3) When the calixarene cavity is modified with boric acid and then encapsulated with melamine anhydride, the calixarene cavity is filled.
[0026] (4) In the early stage of combustion, calixarene boric acid resin produces water vapor and a small amount of boric acid vapor or gas containing element B. These gases can dilute the oxygen concentration in the flame zone, reduce the temperature of the flame, and thus inhibit the combustion reaction. After a small amount of borate decomposes under high temperature (170-220℃), it will form boron oxide (such as B2O3) and borate with aromatic structure. Boron oxide can improve the flame retardant effect to a certain extent, and borate with aromatic structure reacts with the carbonized layer formed by the combustion of benzene ring in calixarene to form a glassy covering layer. Calixarene can form a tighter inclusion complex with the glassy covering layer, which together promotes the formation of a more stable carbonized layer on the surface of the material (calixarene boric acid resin layer), further slowing down the transfer of heat and oxygen, thereby reducing the speed of flame expansion.
[0027] (5) When burning further, the borate will also form a glassy covering layer with the calcium in the hydroxyapatite in the core layer and the aluminum in the aluminum hypophosphite, which together promotes the material to form a more stable carbonization layer, slows down the transfer of heat and oxygen, and reduces the speed of flame expansion.
[0028] (6) In the middle stage of combustion, as the temperature rises (330-350°C), borates will synergistically catalyze the decomposition of the organic melamine phthalic anhydride resin (the products are water, nitrogen oxides, nitrogen, ammonia, etc.), promote the decomposition of melamine phthalic anhydride resin to produce nitrogen (used to dilute the oxygen concentration), ammonia, etc. to dilute the oxygen concentration in the flame zone. Ammonia reacts with free radicals in the combustion zone, especially with hydrogen radicals and hydroxyl radicals (OH·) produced during combustion. This can effectively reduce the concentration of free radicals, inhibit free radical reactions, reduce flame temperature, and thus reduce the rate of the combustion reaction.
[0029] (7) In the later stage of combustion, the N element in melamine phthalic anhydride resin and the phosphorus element in aluminum hypophosphite and hydroxyapatite can play a synergistic flame retardant effect. Aluminum hypophosphite modified with hydroxyapatite will form a relatively stable protective carbonized layer at high temperature. This carbonized layer can effectively block the transfer of oxygen and heat. Aluminum hypophosphite itself can also react with combustion products to generate low-volatile substances (aluminum oxide, aluminum salt). Aluminum hypophosphite can also adsorb nitrogen oxides produced by the decomposition of melamine and react with nitrogen oxides to further reduce the combustion reaction. In addition, the PO bonds in aluminum hypophosphite and hydroxyapatite will break, and phosphorus oxygen free radicals will be generated in the gas phase to capture active hydrogen and hydroxyl free radicals in the pyrolysis process of the polyurethane substrate, inhibiting further cracking and combustion of the PU main chain.
[0030] In order to prevent the flame retardant from being easily damaged in a humid environment and causing the flame retardant performance to deteriorate, a double-layer microcapsule structure flame retardant uses melamine phthalic anhydride resin as the middle shell layer and calixarene boric acid resin as the outer shell layer. The hydroxyapatite-modified aluminum hypophosphite is encapsulated in the cavity formed by the melamine phthalic anhydride resin and the calixarene boric acid resin through the cross-linking interaction and hydrogen bonding interaction between the melamine phthalic anhydride resin and the calixarene boric acid resin.
[0031] Hydroxyapatite is doped into the double-layer microcapsule structure flame retardant. Hydroxyapatite has a synergistic flame retardant effect and gives the material certain seawater corrosion resistance and anti-aging properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 are scanning electron microscope images of the raw materials or products involved in the preparation process of the double-layer microcapsule structure flame retardant in Example 1, a and c are scanning electron microscope images of aluminum hypophosphite, e and f are scanning electron microscope images of melamine phthalic anhydride resin single layer coating (Comparative Example 2), b and d are scanning electron microscope images of the double-layer microcapsule structure flame retardant (Example 1);
[0033] Figure 2 The hydrophobic effect diagram of the flame retardant prepared by the method of the present invention and the flame retardant not prepared by the method of the present invention, a is the aluminum hypophosphite modified polyurethane prepared in Comparative Example 1, and b is the polyurethane modified by the double-layer microcapsule structure flame retardant (Example 1);
[0034] Figure 3 : is the EDS spectrum of the double-layer microcapsule structure flame retardant, a and b are the EDS spectrum of aluminum hypophosphite and the EDS spectrum of the double-layer microcapsule structure flame retardant (Example 1), respectively. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described in detail below through embodiments and drawings.
[0036] Example 1
[0037] A method for preparing a double-layer microcapsule structure flame retardant comprises the following steps:
[0038] SO1, add deionized water at a mass ratio of melamine to deionized water of 1:100 to obtain a melamine aqueous solution; add the melamine aqueous solution (containing 12.6g of melamine) into a three-necked flask, add 37wt% of phthalic anhydride aqueous solution (containing 20.2g of phthalic anhydride) into the melamine aqueous solution, add 25wt% of ammonia water dropwise to adjust the pH to 8.5, react at 80℃ for 1h to obtain a melamine phthalic anhydride resin prepolymer emulsion, add 60g of hypophosphorous acid Aluminum was dispersed in 200 ml of water and added to the prepolymer. 1.5 g of hydroxyapatite (Sigma-Aldrich, N#A8069, the same below) was added to a three-necked flask. The pH was adjusted to 4.5 with acetic acid. The mixture was reacted at 70°C for 4 h, allowed to stand, filtered, washed with anhydrous ethanol until neutral, and dried in an oven at 80°C for 24 h to obtain melamine phthalic anhydride resin-coated hydroxyapatite-modified aluminum hypophosphite microcapsules (MCAHP).
[0039] SO2, add 20g calixarene and 400g N,N-dimethylformamide to the reactor, stir at 60℃ for 2h until the solution is clear; add 60g MCAHP in the first step to the reactor, add 0.5g Tween-80, and stir for 1h. Add 1mol / L boric acid solution (containing 1.1g boric acid) and stir, react at 80℃ for 8h, add 200mL acetone and stir for 30min, cool, filter, wash with acetone until neutral, dry at 80℃ for 24h, grind into powder, and obtain double-layer microcapsule structure flame retardant.
[0040] The preparation method of a flame-retardant polyurethane material comprises the following steps: adding 50 g of a double-layer microcapsule structure flame retardant, 5 g of silica sol, 1 g of propylene glycol, 1 g of sodium carboxymethyl cellulose, and 25 g of choline chloride to 418 g of polyurethane, mixing them evenly, melt-blending them at 180° C., and finally extruding them through a twin-screw extruder, cooling and granulating them to obtain the flame-retardant polyurethane material.
[0041] Example 2
[0042] A method for preparing a double-layer microcapsule structure flame retardant comprises the following steps:
[0043] SO1, add deionized water at a mass ratio of melamine to deionized water of 1:100 to obtain a melamine aqueous solution; add the melamine aqueous solution (containing 12.6g melamine) into a three-necked flask, add 38wt% phthalic anhydride aqueous solution (containing 20.2g phthalic anhydride) into the melamine aqueous solution, add 25wt% ammonia water dropwise to adjust the pH to 8.5, react at 70°C for 1h to obtain a melamine phthalic anhydride resin prepolymer emulsion, disperse 60g aluminum hypophosphite in 200ml water, add to the prepolymer, add 1.5g hydroxyapatite into the three-necked flask, adjust the pH to 4.5 with acetic acid, react at 70°C for 4h, let stand, filter, wash with anhydrous ethanol to neutrality, and dry in an oven at 80°C for 24h to obtain melamine phthalic anhydride resin-coated hydroxyapatite-modified aluminum hypophosphite microcapsules (MCAHP);
[0044] SO2, add 20g calixarene and 400g N,N-dimethylformamide to the reactor, stir at 60℃ for 2h until the solution is clear; add 60g MCAHP in the first step to the reactor, add 0.5g Tween-80, and stir for 1h. Add 1mol / L boric acid solution (containing 1.3g boric acid) and stir, react at 100℃ for 6h, add 200mL acetone and stir for 30min, cool, filter, wash with acetone until neutral, dry at 80℃ for 24h, grind into powder, and obtain double-layer microcapsule structure flame retardant.
[0045] The preparation method of a flame-retardant polyurethane material comprises the following steps: adding 50g of a double-layer microcapsule structure flame retardant, 5g of silica sol, 1g of propylene glycol, 1g of sodium carboxymethyl cellulose, and 25g of choline chloride to 418g of polyurethane, mixing them evenly, melt-blending them at 160°C, and finally extruding them through a twin-screw extruder, cooling and granulating them to obtain the flame-retardant polyurethane material.
[0046] Example 3
[0047] A method for preparing a double-layer microcapsule structure flame retardant comprises the following steps:
[0048] SO1, add deionized water at a mass ratio of melamine to deionized water of 1:100 to obtain a melamine aqueous solution; add the melamine aqueous solution (containing 12.6g melamine) into a three-necked flask, add 39wt% phthalic anhydride aqueous solution (containing 20.2g phthalic anhydride) into the melamine aqueous solution, add 25wt% ammonia water dropwise to adjust the pH to 8.5, react at 80°C for 1h to obtain a melamine phthalic anhydride resin prepolymer emulsion, disperse 60g aluminum hypophosphite in 200ml water, add the prepolymer, add 1.5g hydroxyapatite into the three-necked flask, adjust the pH to 4.5 with acetic acid, react at 80°C for 4h, let stand, filter, wash with anhydrous ethanol until neutral, and dry in an oven at 80°C for 24h to obtain melamine phthalic anhydride resin-coated aluminum hypophosphite microcapsules (MCAHP);
[0049] SO2, add 30g calixarene and 400g N,N-dimethylformamide to the reactor, stir at 60℃ for 2h until the solution is clear; add 60g MCAHP in the first step to the reactor, add 0.5g Tween-80, and stir for 1h. Add 1mol / L boric acid solution (containing 1.6g boric acid) and stir, react at 90℃ for 8h, add 200mL acetone and stir for 30min, cool, filter, wash with acetone until neutral, dry at 80℃ for 24h, grind into powder, and obtain double-layer microcapsule structure flame retardant.
[0050] The preparation method of a flame-retardant polyurethane material comprises the following steps: adding 50g of a double-layer microcapsule structure flame retardant, 5g of silica sol, 1g of propylene glycol, 1g of sodium carboxymethyl cellulose, and 25g of choline chloride to 418g of polyurethane, mixing them evenly, melt-blending them at 200°C, and finally extruding them through a twin-screw extruder, cooling and granulating them to obtain the flame-retardant polyurethane material.
[0051] Example 4
[0052] A method for preparing a double-layer microcapsule structure flame retardant comprises the following steps:
[0053] SO1, add deionized water at a mass ratio of melamine to deionized water of 1:100 to obtain a melamine aqueous solution; add the melamine aqueous solution (containing 12.6g melamine) into a three-necked flask, add 38wt% phthalic anhydride aqueous solution (containing 20.2g phthalic anhydride) into the melamine aqueous solution, add 25wt% ammonia water dropwise to adjust the pH to 8.5, react at 80°C for 1h to obtain a melamine phthalic anhydride resin prepolymer emulsion, disperse 60g aluminum hypophosphite in 200ml water, add the prepolymer, add 1.5g hydroxyapatite into the three-necked flask, adjust the pH to 4.5 with acetic acid, react at 70°C for 4h, let stand, filter, wash with anhydrous ethanol until neutral, and dry in an oven at 80°C for 24h to obtain melamine phthalic anhydride resin-coated aluminum hypophosphite microcapsules (MCAHP);
[0054] SO2, add 20g calixarene and 400g N,N-dimethylformamide to the reactor, stir at 60℃ for 2h until the solution is clear; add 60g MCAHP in the first step to the reactor, add 0.5g Tween-80, and stir for 1h. Add 1mol / L boric acid solution (containing 1.3g boric acid) and stir, react at 100℃ for 8h, add 200mL acetone and stir for 30min, cool, filter, wash with acetone until neutral, dry at 80℃ for 24h, grind into powder, and obtain double-layer microcapsule structure flame retardant.
[0055] The preparation method of a flame-retardant polyurethane material comprises the following steps: adding 50 g of a double-layer microcapsule structure flame retardant, 5 g of silica sol, 1 g of propylene glycol, 1 g of sodium carboxymethyl cellulose, and 25 g of choline chloride to 418 g of polyurethane, mixing them evenly, melt-blending them at 180° C., and finally extruding them through a twin-screw extruder, cooling and granulating them to obtain the flame-retardant polyurethane material.
[0056] Comparative Example 1 (This comparative example does not use double-layer resin to coat aluminum hypophosphite, and does not use hydroxyapatite modification)
[0057] The preparation method of a flame-retardant polyurethane material comprises the following steps: adding 50g of aluminum hypophosphite, 5g of silica sol, 1g of propylene glycol, 1g of sodium carboxymethyl cellulose and 25g of choline chloride into 418g of polyurethane, mixing them evenly, melt-blending them at 180°C, and finally extruding them through a twin-screw extruder, cooling and granulating them to obtain the flame-retardant polyurethane material.
[0058] Comparative Example 2 (This comparative example does not use calixarene boric acid resin to coat MCAHP)
[0059] SO1, add deionized water at a mass ratio of melamine to deionized water of 1:100 to obtain a melamine aqueous solution; add the melamine aqueous solution (containing 12.6g melamine) into a three-necked flask, add 37wt% phthalic anhydride aqueous solution (containing 20.2g phthalic anhydride) into the melamine aqueous solution, add 25wt% ammonia water dropwise to adjust the pH to 8.5, react at 80°C for 1h to obtain a melamine phthalic anhydride resin prepolymer emulsion, disperse 60g aluminum hypophosphite in 200ml water, add to the prepolymer, add 1.5g hydroxyapatite into the three-necked flask, adjust the pH to 4.5 with acetic acid, react at 70°C for 4h, let stand, filter, wash with anhydrous ethanol until neutral, and dry in an oven at 80°C for 24h to obtain melamine phthalic anhydride resin-coated aluminum hypophosphite microcapsules (MCAHP);
[0060] The preparation method of a flame-retardant polyurethane material comprises the following steps: adding 50g of aluminum hypophosphite microcapsules (MCAHP) coated with a single layer of melamine phthalic anhydride resin, 5g of silica sol, 1g of propylene glycol, 1g of sodium carboxymethyl cellulose, and 25g of choline chloride to 418g of polyurethane, mixing them uniformly, melt-blending them at 180°C, and finally extruding them through a twin-screw extruder, cooling and granulating them to obtain the flame-retardant polyurethane material.
[0061] Comparative Example 3 (No flame retardant was used in this comparative example)
[0062] The preparation method of a flame-retardant polyurethane material comprises the following steps: adding 5 g of silica sol, 1 g of propylene glycol, 1 g of sodium carboxymethyl cellulose and 25 g of choline chloride to 468 g of polyurethane, mixing them uniformly, melt-blending them at 180° C., and finally extruding them through a twin-screw extruder, cooling and granulating them to obtain the flame-retardant polyurethane material.
[0063] Comparative Example 4 (In this comparative example, calixarene is replaced with chitosan)
[0064] In this comparative example, calixarene is replaced by chitosan, and the rest is the same as in Example 1.
[0065] Comparative Example 5 (this comparative example does not add boric acid)
[0066] The step of “adding 1 mol / L boric acid solution (containing 1.1 g of boric acid) and stirring” was omitted, and the rest was the same as in Example 1.
[0067] Comparative Example 6 (This comparative example modifies the mass ratio of aluminum hypophosphite to melamine)
[0068] In this comparative example, the addition amount of aluminum hypophosphite is 30 g, the mass ratio of aluminum hypophosphite to melamine is 30:12.6 (equivalent to 2.38:1), and the rest are the same as in Example 1.
[0069] Comparative Example 7 (This comparative example modifies the mass ratio of calixarene to MCAHP)
[0070] In this comparative example, the addition amount of calixarene is 10 g, the mass ratio of calixarene to MCAHP is 1:6, and the rest is the same as in Example 1.
[0071] Comparative Example 8 (This comparative example modifies the reaction temperature of S01)
[0072] 25 wt % ammonia water was added dropwise to adjust the pH to 8.5, and the reaction was carried out at 90° C. for 1 h. The rest of the reaction was the same as in Example 1.
[0073] Comparative Example 9 (In this comparative example, aluminum hypophosphite is not coated with melamine phthalic anhydride resin, but aluminum hypophosphite is directly coated with calixarene boric acid resin)
[0074] A method for preparing a microcapsule structure flame retardant comprises the following steps:
[0075] SO1, add 20g calixarene and 400g N,N-dimethylformamide to the reactor, stir at 60℃ for 2h until the solution is clear; disperse 60g aluminum hypophosphite and 1.5g hydroxyapatite in 200ml water, add to the reactor, add 0.5g Tween-80, stir for 1h. Add 1mol / L boric acid solution (containing 1.1g boric acid) and stir, react at 80℃ for 8h, add 200mL acetone and stir for 30min, cool, filter, wash with acetone until neutral, dry at 80℃ for 24h, grind into powder, and obtain microcapsule structure flame retardant.
[0076] The preparation method of a flame-retardant polyurethane material comprises the following steps: adding 50g of a microcapsule structure flame retardant, 5g of silica sol, 1g of propylene glycol, 1g of sodium carboxymethyl cellulose and 25g of choline chloride into 418g of polyurethane, mixing them uniformly, melt-blending them at 180°C, and finally extruding them through a twin-screw extruder, cooling and granulating them to obtain the flame-retardant polyurethane material.
[0077] Comparative Example 10 (this comparative example removes the core layer)
[0078] SO1, add deionized water at a mass ratio of melamine to deionized water of 1:100 to obtain a melamine aqueous solution; add the melamine aqueous solution (containing 12.6g of melamine) into a three-necked flask, add a 37wt% phthalic anhydride aqueous solution (containing 20.2g of phthalic anhydride) to the melamine aqueous solution, dropwise add 25wt% ammonia water to adjust the pH to 8.5, react at 80°C for 1h to obtain a melamine phthalic anhydride resin prepolymer emulsion, let stand, filter, wash with anhydrous ethanol until neutral, and dry in an oven at 80°C for 24h to obtain a melamine phthalic anhydride resin;
[0079] SO2, add 20g calixarene and 400g N,N-dimethylformamide to the reactor, stir at 60℃ for 2h until the solution is clear; add 60g melamine phthalic anhydride resin in the first step to the reactor, add 0.5g Tween-80, and stir for 1h. Add 1mol / L boric acid solution (containing 1.1g boric acid) and stir, react at 80℃ for 8h, add 200mL acetone and stir for 30min, cool, filter, wash with acetone until neutral, dry at 80℃ for 24h, grind into powder, and obtain microcapsule structure flame retardant.
[0080] The preparation method of a flame-retardant polyurethane material comprises the following steps: adding 50g of a microcapsule structure flame retardant, 5g of silica sol, 1g of propylene glycol, 1g of sodium carboxymethyl cellulose and 25g of choline chloride into 418g of polyurethane, mixing them uniformly, melt-blending them at 180°C, and finally extruding them through a twin-screw extruder, cooling and granulating them to obtain the flame-retardant polyurethane material.
[0081] The flame retardant polyurethane materials prepared in Examples 1-4 and Comparative Examples 1-10 were tested for performance, and the results are shown in Table 1. The limiting oxygen index test was conducted on an oxygen index meter 1600 according to GB / T2406-2009; the flammability test of the specimens was conducted on a horizontal vertical combustion tester CZF-5A according to UL94 standard; the mechanical properties of the materials were examined using an electronic universal testing machine, and the tensile properties were tested according to the Chinese national standard GB528-2009, with a tensile rate of 25 mm / min.
[0082] Table 1 Test results of flame retardant polyurethane materials obtained in Examples 1-4 and Comparative Examples 1-10
[0083]
[0084] From the data of Example 1 and Comparative Example 1, it can be seen that the flame retardant performance of the flame retardant modified polyurethane coated with double-layer microcapsules is significantly enhanced, the LOI value is increased from 21.5% to 34.4%, and the flame retardant grade is increased from UL 94V-1 to UL94V-0. In addition, the tight coating, cross-linking, hydrogen bonding and hydroxyapatite in the double-layer microcapsules synergistically improve the mechanical properties.
[0085] Comparative Example 2 does not use calixarene boric acid resin to coat MCAHP, and the flame retardant core component MCAHP has no coating, and LOI is significantly reduced. Without calixarene boric acid resin, there is no crosslinking in the structure, and hydrogen bonding is significantly reduced, so the mechanical properties are also reduced.
[0086] In comparative example 3, the polyurethane which has not been modified with a flame retardant was subjected to vertical combustion and limiting oxygen index tests. Since it was completely burned and destroyed during the test, it continued to burn for a long time, producing 8 to 9 droplets, and these droplets could ignite the absorbent cotton. Therefore, the UL-94 test could not be carried out and the flame retardant performance was poor.
[0087] Compared with Comparative Examples 1 and 2, Example 1 has significantly enhanced flame retardant properties, with the flame retardant grade raised to UL-94V-0, and no molten droplets fall compared with Comparative Example 3, showing stronger flame retardant properties.
[0088] In Comparative Example 4, compared with Example 1, calixarene is replaced with chitosan. Since chitosan does not contain a cavity, the relative amount of chitosan required to form an effective coating is significantly larger, so the coating effect is slightly inferior when the amount remains unchanged; chitosan does not contain an aromatic structure and cannot undergo a Π-Π stacking effect with melamine phthalic anhydride, and chitosan is highly hydrophilic and repels melamine phthalic anhydride, which has a strong hydrophobicity, so it cannot achieve tight coating and the mechanical properties are also reduced.
[0089] Compared with Example 1, Comparative Example 5 has a lower limiting oxygen index due to the absence of boric acid.
[0090] Compared with Example 1, Comparative Example 6 modified the mass ratio of aluminum hypophosphite to melamine, reduced the content of aluminum hypophosphite in the core layer, and reduced the phosphorus content of the overall flame retardant. During the flame retardant process, phosphorus combined with free radicals, and the free radical reaction during the flame retardant combustion process was weakened, resulting in a decrease in the limiting oxygen index. The mechanical properties were also reduced.
[0091] Compared with Example 1, Comparative Example 7 modified the mass ratio of calixarene to MCAHP, making the calixarene less, resulting in the inability of calixarene to fully coat the melamine phthalic anhydride resin, and the flame retardant properties and mechanical properties decreased to a certain extent. The mass ratio of calixarene to MCAHP is also important for the calixarene boric acid resin and melamine phthalic anhydride resin to synergistically improve the hydrophobicity, and the hydrophobicity also decreased.
[0092] Compared with Example 1, in Comparative Example 8, the reaction temperature in S01 was modified, which affected the polymerization effect of the melamine phthalic anhydride resin prepolymer, resulting in a decrease in the limiting oxygen index and the mechanical properties.
[0093] Compared with Example 1, Comparative Example 9 does not use melamine phthalic anhydride resin to coat aluminum hypophosphite, but directly coats aluminum hypophosphite with calixarene boric acid resin. Due to the lack of melamine phthalic anhydride resin, the flame retardancy is significantly reduced; and there is no cross-linking in the structure of Comparative Example 9, the hydrogen bonding is significantly reduced, and the mechanical properties are also significantly reduced.
[0094] Compared with Example 1, the flame retardant properties of Comparative Example 10 are significantly reduced, and the mechanical properties are also reduced because the core layer is deleted.
[0095] Among them, what improves or maintains the mechanical properties in the material are the polymers in the shell and the mutual cross-linking and hydrogen bonding between the polymers. The mechanical properties will be reduced to a certain extent if the shell is reduced or the ratio is not optimal.
[0096] The water contact angles of the surfaces of Examples 1 to 4 were measured and compared with Comparative Examples 1 to 10. The detection process was as follows: at room temperature, a droplet with a volume of 5 μL was used to measure the contact angle of the sample surface using an optical goniometer (JC2000D3R, Shanghai Zhongchen Digital Technology Instrument Co., Ltd., China).
[0097] Table 2 Contact angles of embodiments and comparative examples
[0098] Example Contact angle (°) Example 1 132.4 Comparative Example 1 72.5 Example 2 130.5 Comparative Example 2 115.5 Example 3 134.8 Comparative Example 3 92.1 Example 4 130.6 Comparative Example 4 74.5 Comparative Example 5 133.5 Comparative Example 6 132.6 Comparative Example 7 125.3 Comparative Example 8 130.5 Comparative Example 9 112.5 Comparative Example 10 135.6
[0099] From the data in Table 1 and Table 2, it can be seen from Example 1 and Comparative Example 4 that although replacing calixarene with chitosan has a certain coating effect and similar flame retardant properties, the hydrophobicity is significantly reduced and does not meet the application requirements.
[0100] Compared with Example 1, since Comparative Example 2 does not use calixarene boronic acid resin to coat MCAHP, it is impossible to form a Π-Π stacking effect and cannot synergistically improve the hydrophobicity with the calixarene boronic acid resin, so the hydrophobicity decreases.
[0101] Compared with Example 1, the hydrophobicity of Comparative Example 3 is significantly reduced due to the lack of flame retardant modification.
[0102] In Comparative Example 8, the reaction temperature is too high. During the prepolymerization of the melamine phthalic anhydride resin, the degree of polymerization is high, which is not conducive to the subsequent coating, so the hydrophobic angle is slightly reduced.
[0103] It can be seen from Example 1 and Comparative Example 9 that the hydrophobicity of the flame retardant with a single-layer microcapsule structure is significantly reduced, and the double-layer coating can achieve a better coating effect through the hydrophobicity of the shell layer and the tight cross-linking of the double shell layer, which can synergistically play a better hydrophobic role.
[0104] It can be seen from Example 1 and Comparative Example 1 that the hydrophobicity of the flame retardant modified polyurethane without double-layer resin coating of aluminum hypophosphite is also significantly reduced due to the hydrophilicity of aluminum hypophosphite itself.
[0105] Figure 1 The scanning electron microscope images of the raw materials or products involved in the preparation process of the double-layer microcapsule structure flame retardant in Example 1. a and c are scanning electron microscope images of aluminum hypophosphite, e and f are scanning electron microscope images of melamine phthalic anhydride resin single layer coating (Comparative Example 2), it can be clearly seen that melamine phthalic anhydride resin is polymerized on the surface of aluminum hypophosphite, b and d are scanning electron microscope images of the flame retardant after double-layer microencapsulation (Example 1), after layer-by-layer coating assembly, it can be clearly seen that the prepared double-layer microcapsule coated flame retardant is successfully prepared.
[0106] Figure 2 The hydrophobic effect diagram of the flame retardant prepared by the method of the present invention and the flame retardant not prepared by the method of the present invention, a is the aluminum hypophosphite modified polyurethane prepared in Comparative Example 1, b is the polyurethane modified by the double-layer microcapsule structure flame retardant (Example 1), and it can be found from the comparison that the contact angle of the double-layer microcapsule modified polyurethane prepared by the present method is greater than 130 degrees, and the hydrophobicity is relatively strong;
[0107] Figure 3 This is the EDS energy spectrum of the double-layer microcapsule structure flame retardant in Example 1. a and b are the EDS energy spectrum of aluminum hypophosphite and the EDS energy spectrum of the double-layer microcapsule structure flame retardant (Example 1), respectively. It can be clearly seen that the N element is coated in the shell layer, confirming the successful preparation of the double-layer microcapsule structure flame retardant.
[0108] It should be understood that the above embodiments do not limit the present invention in any form, and any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the protection scope of the present invention.
Claims
1. A double-layer microcapsule structure flame retardant, characterized in that: It comprises an outer shell layer, a middle shell layer and a core layer arranged from the outside to the inside; wherein the outer shell layer is calixarene boric acid resin, the middle shell layer is melamine phthalic anhydride resin, and the core layer is hydroxyapatite-modified aluminum hypophosphite.
2. The method for preparing a double-layer microcapsule structure flame retardant according to claim 1, characterized in that: The steps include: SO1, add melamine aqueous solution into the reaction kettle, add phthalic anhydride aqueous solution with a mass fraction of 37wt% to 39wt% into the melamine aqueous solution, so that the molar ratio of phthalic anhydride to melamine is 3:2.15-2.22, add nitrogen-containing pH regulator dropwise to adjust the pH to 8-9, react at 65-80°C for 0.5-1.5h to obtain melamine phthalic anhydride resin prepolymer emulsion, then add aluminum hypophosphite and hydroxyapatite to the melamine phthalic anhydride prepolymer emulsion at a mass ratio of aluminum hypophosphite to melamine of 3-6:1 and a mass ratio of hydroxyapatite to melamine of 1:8-12, adjust the pH to 4-5 with an acidic pH regulator, react at 70-90°C for 4-6h, let stand, filter, wash with anhydrous ethanol to neutrality, and dry at 60-95°C for 12-24h to obtain melamine phthalic anhydride resin-coated modified aluminum hypophosphite microcapsules (MCAHP); SO2, mix calixarene with N,N-dimethylformamide in a mass ratio of 1:20-40, stir at 60-90℃ for 1-2h, until the solution is clear; then add MCAHP in a mass ratio of 2-4:1 to calixarene, add Tween-80, stir for 0.5-1h, add boric acid in a mass ratio of boric acid to calixarene of 1:15-20, stir, react at 80-105℃ for 5-8h, add acetone in a mass ratio of MCAHP to acetone of 1:3-5 and stir for 30min, cool, filter, wash with acetone until neutral, dry at 80-120℃ for 24-48h, grind into powder, and obtain a double-layer microcapsule structure flame retardant.
3. The method for preparing a double-layer microcapsule structure flame retardant according to claim 2, characterized in that: In SO1, the nitrogen-containing pH adjuster is one of ammonia water, ammonium chloride and ammonium carbonate.
4. The method for preparing a double-layer microcapsule structure flame retardant according to claim 2, characterized in that: In SO1, the acidic pH adjuster is one of acetic acid, hydrochloric acid and sulfuric acid.
5. A flame-retardant polyurethane material prepared using the double-layer microcapsule structure flame retardant according to claim 1.
6. The method for preparing the flame retardant polyurethane material according to claim 5, characterized in that: The method comprises the following steps: uniformly mixing the components with polyurethane according to the addition amount of 10wt% to 20wt% of a double-layer microcapsule structure flame retardant, 0.5wt% to 1wt% of silica sol, 0.1wt% to 0.25wt% of a film-forming aid, 0.1wt% to 0.25wt% of a thickener and 5wt% to 10wt% of an ion conductive agent, melt blending at 160 to 200°C, and finally extruding through a twin-screw extruder and cooling and granulating to obtain a flame-retardant polyurethane material.
7. The method for preparing a flame retardant polyurethane material according to claim 6, characterized in that: The mass fraction of SiO2 in the silica sol is 20%±2%; the thickener is one of alkyl ammonium salt, gelatin or sodium carboxymethyl cellulose; and the film-forming aid is one of propylene glycol, propylene glycol butyl ether, dodecyl alcohol ester or N,N-dimethylformamide.
8. The method for preparing a flame retardant polyurethane material according to claim 6, characterized in that: The ion conductive agent is a combination of one or more of choline chloride, acetylcholine chloride and carbachol.
9. Use of the double-layer microcapsule structure flame retardant according to claim 1 or the flame retardant polyurethane material according to claim 5 in combustible gas transmission pipelines, marine pipelines and shale gas fracturing pipelines.
Citation Information
Patent Citations
Preparation method and application of phosphorus-nitrogen containing intumescent flame retardant nanosheet
CN115246860A
Flame retardant with capsule core structure, preparation method and application thereof
CN110964347A
Preparation method of inorganic aluminum hypophosphite and application of inorganic aluminum hypophosphite in flame-retardant PBT (polybutylene terephthalate)
CN114085422A
Double-layer microencapsulated red phosphorus flame retardant containing cyclodextrin as well as preparation method and application of double-layer microencapsulated red phosphorus flame retardant
CN114196074A
Preparation method of double-layer coated ammonium polyphosphate flame retardant
CN116376114A
Cited By
Flame retardant, preparation method thereof and application of flame retardant in polyvinyl chloride
CN120118390A
A flame retardant, its preparation method and its use in polyvinyl chloride
CN120118390B
Flame-retardant protective composite coating for pipeline and preparation method of flame-retardant protective composite coating
CN121086596A